Geopolitics and International Sports Governance: a Case Study of FIFA's Response to the Russian and Israeli National Teams Amid Russia's Versus Ukraine and Israel's Versus Palestine Rage - Muhammad Farkhan Ghifari; Bambang W. Nugroho (Publikasi Indonesia, 2025)
This article analyzes the response of the Federation Internationale de Football Association (FIFA) to two major geopolitical conflicts, namely the Russia–Ukraine war and the Israeli–Palestinian conflict, by examining the differences in attitudes applied to the Russian and Israeli national teams. This study uses a qualitative comparative case study method by integrating a review of academic literature, analysis of official FIFA documents, and a reading of global geopolitical dynamics to evaluate the consistency of the application of the principles of neutrality, non-discrimination, and governance of international sports organizations. The findings suggest that the imposition of blanket sanctions against Russia, compared to the non-imposition of sanctions against Israel, reflects the inconsistency of FIFA's stance which is more accurately understood as a form of politicized neutrality than as normative discrimination. Furthermore, the findings indicate that FIFA's stance is influenced by external geopolitical pressures, global power configurations, and pragmatic considerations of the organization in maintaining its legitimacy and stability. These findings reveal the limitations of claims of sports neutrality within the framework of global governance and affirm that international sports organizations are not completely autonomous from international dynamics. Thus, this article contributes to international relations and sports governance through the development of an analytical framework on the relationship between normative principles, geopolitical interests, and power structures in FIFA's decision-making process.